The Cambridge companion to Francis of Assisi. - Robson, Michael J.P. (Cambridge Cambridge university press, 2012)
"Francis of Assisi (1181/82-1226) was one of the most vibrant and colourful personalities in the Middle Ages. The life of this remarkable reformer of the medieval Church was celebrated in art, drama, poetry, music, the new vernacular literature and architecture. His ideal was to enter into a restorative and enriching relationship with Jesus Christ, whom he wished to imitate in the most perfect manner, a direct and immediate goal which captured the contemporary imagination. This Companion explores the life of Francis of Assisi and his enduring legacy throughout the centuries. The first part concentrates on his life and works whilst the second explores the way in which his heritage influenced the apostolic activities of his followers in the century following his death. This book is a must-read for students and scholars of Church history, as well as medieval social and intellectual history"--
Part I. Francis of Assisi: 1. Francis and the Franciscan movement (1181/2-1226) / Michael F. Cusato -- 2. The writings of Francis / Michael J.P. Robson -- 3. The Rule and life of the Friars Minor / William J. Short -- 4. Francis and his hagiographical tradition / Michael W. Blastic -- 5. Voluntary simplicity: the attitude of Francis towards learning in the early biographies / Neslihan Şenocak -- 6. Francis and the historiographical tradition in the order / Annette Kehnel -- 7. Francis and Clare and the emergence of the Second Order / Jean François Godet-Calogeras -- 8. Francis and the encounter with the sultan (1219) / Steven J. McMichael -- 9. Francis and creation / Timothy J. Johnson -- Part II. The Heritage of Francis of Assisi: 10. Francis and the pursuit of learning / Bert Roest -- 11. The early Franciscans and the towns and cities / Jens Röhrkasten -- 12. The Third Order of Francis / Ingrid Peterson -- 13. Franciscan ideals and the royal family of France (1226-1328) / Sean L. Field -- 14. Franciscans as papal and royal envoys to the Tartars (1245-1255) / Peter Jackson -- 15. Franciscan missions / E. Randolph Daniel -- 16. Pope John XXII, the Franciscan order and its Rule / Patrick Nold -- 17. The ecumenical appeal of Francis / Petà Dunstan.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; 271.3-4 -- Franciscanen. Minderbroeders: stichter; stichting; regels; statuten; 929 FRANCISCUS ASSISIENSIS -- Biografie. Genealogie. Heraldiek--FRANCISCUS ASSISIENSIS